Therapists’ views on working with bilingual Spanish-English clients: A qualitative inverstigation - Santiago-Rivera, Azara. L.; Altarriba, Jeanette; Poll, Norma; Gonzalez-Miller, Normaris; Cragun, Cragun (Professional Psychology: Research and Practice, 2009)
Through semistructured interviews, language switching in therapy was examined with 9 bilingual Spanish and English therapists. Therapists were asked about how and when they switched from one language to another during treatment, as well as the ways in which their clients’ switched languages. After the use of consensual qualitative research methods (C. E. Hill et al., 2005; C. E. Hill, B. J. Thompson, & E. N. Williams, 1997), the results revealed that therapists used language switching as a mechanism to establish trust, bond with clients, and promote disclosure through the use of specific phrases or specific words; particularly, the use of Spanish idiomatic expressions (dichos) served to engage, redirect, and increase client self-understanding and awareness. Therapists reported that their clients switched from English to Spanish when recounting experiences that involved certain emotions (e.g., anger) and represented themselves differently depending on the language they were speaking. Therapists also reported that their clients switched from English to Spanish to improve communication and to connect with them. Future directions for research and implications for training and practice are outlined. (PsycInfo Database Record (c) 2025 APA, all rights reserved)